Newlyweds take the UMP convocation stage - Nor Salwana, Mohammad Idris (2022)
PAYA BESAR, 6 November 2022 – The newlyweds, Muhammad Shafinaim Akmal Zukifli and Nur Shahida Azzahra Mohd Zamri shared their double joy when sharing the stage at the 17th Universiti Malaysia Pahang (UMP) Convocation Ceremony a day after their wedding ceremony.